LOGISTICS MANAGEMENT SYSTEMS AND PERFORMANCE OF FAST-MOVING CONSUMER GOODS MANUFACTURERS IN NAIROBI, KENYA - Jepherson, Muhalia; Ngugi, Patrick; Moronge, Makori (International Journal of Supply Chain Management, 2021)
Purpose: The purpose of this study was to establish the relationship between logistics management systems and supply chain performance of fast-moving consumer goods manufacturers in, Kenya Methodology: The study used descriptive research design was The study targeted the operations managers of the 51 FMCG manufacturers located in Nairobi. The sample size was 51 respondents who were selected using the census method. Questionnaires were used for data collection. For comprehension, logic and relevance, 5 respondents were used in pre-testing the questionnaire. Descriptive statistics will be used to analyze quantitative data. In order to test the significance of the effect of the predictor variables on response variables, the study used multiple linear regressions. Data collected was analyzed using SPSS version 23 and presentation of the findings done using figures, tables and charts. Results: The study found that warehouse management systems positively and significantly influences Supply chain performance of FMCG in Kenya; inventory management systems positively and significantly influences Supply chain performance of FMCG in Kenya; transportation management systems positively and significantly influence Supply chain performance of FMCG in Kenya; clearing and forwarding management systems have positive significant relationship with Supply chain performance of FMCG in Kenya; and information technology has a positive significant influence on the relationship between logistics management systems and supply chain performance of FMCG manufacturers in Kenya. Unique contribution to theory, practice and policy: The study recommends management of the company to ensure they remain informed on the changes in the market to ensure that their warehouse management system is up-to-date and therefore avoid process redundancy and inaccurate inventories. There is a need to use strategic approach in practices of managing logistics by embracing modernized technology and training of employees on the use of the same. Companies should automate their scheduling process this will lead to fewer interventions by the management and therefore lowering any chances of delays. It is also important for the government to ensure that there are clear regulations by custom department and ensure that the employees in this department are well knowledgeable of their task and are well organized and motivated to conduct their duties.